Questioning The Existence Of Asean Political Security Community In South China Sea Conflict - Renaldo Benarrivo; Teguh Puja Pramadya (Global Political Studies Journal, 2020)
South China sea conflicts continue to escalate and increase the significance of the countries in Southeast Asia. This potentially have an impact on the stability of regional security systemically. Asean Political Security Community (APSC) as an important part of regional governance certainly needs to take a role. However, ASEAN member countries tend to still use their own methods, and have not optimally used the APSC as a means to increasing their bargaining position over the ongoing conflict. The use of the constructivism approach in this paper will try to explore how APSC should be able to play a more operational role and positioning itself as the only security community in the region. Qualitative research methods are used to interpret any phenomena that occur related to the involvement of Southeast Asian countries in the South China Sea conflict. This paper questioning the existence ofAPSC with its formality in responding various kinds of issues and the latest security dynamics in Southeast Asia, especially the South China Sea Conflict. The underlying causes for APSC's nongrounded policy direction will be part of the conclusion of this paper.